Accounting ethics - Duska, Ronald F., 1937-; Duska, Brenda Shay.; Ragatz, Julie (Chichester, West Sussex, U.K. ; Malden, MA : Wiley-Blackwell, 2011)
This new edition of Accounting Ethics has been comprehensively updated to deal with the significant changes within the accounting profession since 2002; the authors systematically explore the new range of ethical issues that have arisen as a result of recent developments, including the financial crisis of 2008. It highlights the debates over the use of fair-value accounting and principles- versus rules-based standards; offers a comprehensive overview of ethics in accounting, as well as an examination of and recommendations for solving the current crisis in this field; investigates the nature and purpose of accounting; uses concrete examples and case studies, including current situations; and, examines the ethical responsibilities of individual accountants as well as accounting firms.
The nature of accounting and the chief ethical difficulty: true disclosure -- Ethical behavior in accounting: what is ethics? -- Ethical behavior in accounting: ethical theory -- Accounting as a profession: characteristics of a profession -- Accounting codes of conduct -- The rules of the code of conduct -- The auditing function -- The ethics of managerial accounting -- The ethics of tax accounting -- Ethics applied to the accounting firm -- Afterword: current debates on accounting issues -- Appendix A: Summary of the Sarbanes-Oxley Act of 2002 -- Appendix B: The IMA Code of Conduct for management accountants.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Accountants -- Professional ethics; Accounting -- Moral and ethical aspects; Accountants -- Professional ethics; Accounting -- Moral and ethical aspects; Accounting; Bedrijfsethiek; Electronic books; Electronic books